EDUKASI SENAM KAKI DIABETIK TERHADAP PENURUNAN ANKLE BRACHIAL INDEX (ABI) PADA PASIEN DIABETES MILITUS DI DESA LINGGA - Fatayati, Imma; Suwandi, Edy; Ikhsan, Bagus Muhammad (MAJU : Indonesian Journal of Community Empowerment, 2025)
Diabetes mellitus can lead to various complications, including peripheral circulation disorders indicated by a decrease in the Ankle Brachial Index (ABI), which may result in amputation. Data from Lingga Public Health Center in 2023 recorded approximately 186 people with diabetes, with an increasing trend each year. Prevention of diabetic foot complications can be achieved through education and simple physical activities such as diabetic foot exercises. This community service aimed to improve diabetic patients’ understanding of ABI reduction through diabetic foot exercises in Lingga Village. The methods included education, exercise training, ABI examination, and evaluation of understanding and implementation. The results showed an 85% increase in participants’ understanding of ABI examination and diabetic foot exercises. In conclusion, there was an improvement in patients’ knowledge, which is expected to serve as a promotive and preventive effort to reduce the risk of diabetic foot complications.